PENGARUH IMPLEMENTASI HR ANALYTICS TERHADAP PENGAMBILAN KEPUTUSAN STRATEGIS DALAM MANAJEMEN SDM PADA PT. XYZ - Abu Bakar Akbar; Nadia Adrine Ricadonna; Asih Handayani; Fatimah Azahra (JURNAL ILMIAH EDUNOMIKA, 2026)
The development of digital technology and big data has transformed the paradigm of human resource management in modern organizations. One increasingly prominent approach is Human Resource Analytics (HR Analytics), which involves the utilization of data and analytical techniques to enhance the effectiveness of decision-making in human resource management. This study aims to analyze the effect of HR Analytics implementation on strategic decision-making in human resource management at PT. XYZ. The study employs a quantitative approach with a survey method targeting employees and HR practitioners at PT. XYZ. The research sample consists of 120 respondents selected using purposive sampling. Data analysis was conducted using simple linear regression to examine the relationship between HR Analytics implementation and the quality of strategic decision-making. The results indicate that the implementation of HR Analytics has a positive and significant effect on strategic decision-making in human resource management at PT. XYZ. Systematic utilization of employee data enhances the accuracy of decisions related to recruitment, employee development, and performance management. The findings imply that organizations need to improve analytical competencies as well as technological infrastructure to optimize the use of HR Analytics in supporting organizational strategies.